IMPLEMENTATION OF THE ELECTRONIC OFFICIAL DOCUMENT APPLICATION PROGRAM E-BUDDY IN THE SUMORAME VILLAGE GOVERNMENT - Khasanah, Ushwatun; Rodiyah, Isnaini (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the implementation of the E-Buddy electronic official script application in enhancing administrative efficiency within the Government of Sumorame Village, Sidoarjo Regency. Method: Employing a descriptive qualitative approach, data were collected through interviews, observations, and documentation, and analyzed using Mazmanian and Sabatier’s policy implementation theory, which emphasizes policy clarity, resources, implementer disposition, and bureaucratic structure. Results: The findings reveal that while the E-Buddy application represents a step toward digital governance, its implementation encounters significant obstacles, including limited human resources, inadequate internet infrastructure, insufficient training and socialization, and resistance from village officials toward digital transformation. These challenges hinder the consistency and effectiveness of the application in achieving its intended outcomes. Novelty: This study provides a unique contribution by applying Mazmanian and Sabatier’s framework to evaluate digital innovation at the village governance level, highlighting the practical barriers and policy determinants that influence implementation. The analysis underscores the need for strategic interventions such as capacity building, infrastructure reinforcement, and the establishment of a dedicated coordination team to ensure the sustainability and scalability of the E-Buddy application in supporting rural administrative reform